Rational Choice Theory Applied to an Explanation of Juvenile Offender Decision Making in the Chinese Setting - Zhao, Jihong (International journal of offender therapy and comparative criminology, 2021)
Rational choice theory (RCT) is a classical theory in criminology, with deep roots in the Enlightenment. It has secured a privileged place as a mainstream criminological theory in the United States. Ironically, RCT has not been applied to research on juvenile delinquency and related decision making in China. This study attempts to test the relative utility of RCT among adjudicated juvenile offenders incarcerated in an institution located in a southwestern province of China based on their responses to two hypothetical scenarios of offending. The results of the Tobit model analyses emerged from the two-wave longitudinal data lent strong support to the view that RCT can indeed serve as an important theory for explaining delinquent behaviors in China. More specifically, juvenile offenders used cost-benefit analysis to decide if they want to be involved either in the stealing scenario or in the fighting scenario. A discussion of findings and public policy implications are highlighted at the end of the paper